Identifying Gaps Between Theory and Clinical Practice Among Fourth-Year Nursing Students for Skill Enhancement - Angue, Jairah Kaye; Barrieta , Karyle Ella P.; Brar, Sahib Jeet J.K.; Dimayuga , Bryan S.A; Maganes , Melanie Marie O.; Mondina , Jewel Grecelyn F.; Merced , Joel John A. Dela; Guevarra , Cecile F.; Reyes , Juvy G.; Arreglo , Elenita M.; Grageda , Florence B.; Lopez , Mary Ann E.; Abendanio , Emerita M.; Sedeno , Carlos Kurt S. (Celebes Nursing Journal, 2025)
The theory-practice gap, a significant issue in nursing education, has been a primary concern for student nurses worldwide. Despite its importance, many nursing students struggle to connect theoretical knowledge with clinical practice, leading to gaps in their understanding and skills. This phenomenon has been observed in various countries, including India, the Philippines, and others. This qualitative study aims to investigate the theory- practice gap among selected fourth-year nursing students, exploring the reasons behind the misalignment between theoretical concepts and clinical exposures. The researchers employed a phenomenological research design centered on comprehending people's lived experiences and the phenomena that have influenced them. The researchers interviewed fifteen (15) fourth-year nursing students chosen for the video and audio recording in-depth interview by following the inclusion and exclusion criteria. With this, the researchers sought the assistance of a qualitative expert by utilizing NVivo software to extract significant statements and merge them into themes for thematic analysis. Based on the findings, the discrepancies are caused by several factors: student readiness, equipment availability, unfamiliar procedures, heavy workloads, and adaptability to the clinical settings, in addition to variations between instruction in the skills laboratory and clinical practice. Generally, the study has identified the gaps between integrating theoretical concepts and clinical exposure. Considering the identified gaps, the researchers recommended five nursing programs related to skill enhancements that adapt to changing demands in the healthcare industry, provide long-term knowledge and skills, and develop innovative education strategies that could upgrade the overall quality of nursing care.